Understanding how professional development opportunities affect open educational resource sharing - Flowers, Sharleen; Hazlett, Zachary S.; Ramirez, Marie; Treibergs, Kira; Vinson, Erin; Smith, Michelle K.; Knight, Jennifer K. (Frontiers in Education, 2024)
Open Educational Resources (OERs) help instructors create innovative lessons and foster costeffective and equitable access to educational materials. As more instructors turn to OERs to enhance their courses, there is a growing demand for the creation of more lesson plans. To increase the number of high-quality OERs in undergraduate biology and physics, the journal CourseSource introduced Writing Studios to assist educators in writing and publishing OERs. Over a period of five years, 188 attendees participated in Writing Studios and followed a scaffolded worksheet to help draft their OER and engaged in peer-review with partners. However, only a subset shared their OERs through a CourseSource publication. Here we explore what characteristics predict whether participants share their OERs through a CourseSource publication, in what ways does participation in a CourseSource Writing Studio help participants achieve their goals, and what long-term supports participants perceive are necessary to successfully share their work through publication. This study highlights the importance of ongoing support and tailored strategies to facilitate the sharing of OERs and the findings can benefit instructors and professional development leaders who are committed to increasing the number of high-quality resources that are available.